Trends and Patterns of The Internet Use During School Holidays - Khalid, Khalid; Rozas, Indri Sudanawati; Rolliawati, Dwi (Journal of Information Systems Engineering and Business Intelligence, 2020)
Background: The Internet use according to Indonesian Internet Services Provider Association (APJII) can be an indicator for parents and educators to monitor students’ mental development and learning behaviors. Objective: This study aims to analyze trends and patterns of the Internet use among students during the school holidays. Methods: This study uses data from XYZ operator, one of the most affordable mobile service providers in Indonesia in 2019. The data was analyzed by using Online Analytical Processing (OLAP). Result: The results shows that the use of 3G and 4G data increased significantly during the school holidays, compared to school days. The highest increase of the Internet traffic is during the semester break, occurred at the rate of 22 to 24 hours a day, with the peak reaching 20.87% at 10:00. Conclusion: The research findings can inform relevant parties, both parents and school teachers in guiding their children to use the Internet.